Innovation and Practice of Students’ Evaluation of Teaching - Wang, Feng (Journal of Theory and Practice of Social Science, 2024)
Students' evaluation of teaching is to establish a platform between students and teachers, which can make them fully trust, so as to convey the real feelings of students and teachers, and improve the quality of teaching. However, in the actual implementation process, we pay too much attention to the evaluation of teaching results, which leads to the failure of the evaluation mechanism, which also leads to the failure of students' evaluation system. However, this does not mean that the student evaluation system itself is not good, this paper will analyze the existing shortcomings of the domestic university rating mechanism, and then give the solution strategy. At present, the innovation and ideological and political teachers in higher vocational schools still lack an effective training and performance evaluation system, and also ignore the era of "post class competition and certification", as well as the demand for knowledge and innovation ability of university teachers. Teachers are ordinary people and have great laziness. Teachers are not omnipotent. The quality of education cannot meet the requirements only by consciously lacking the restriction of system and evaluation mechanism.